Correlation Between Gender, Age, and Body Mass Index with Length of Stay in Nephrolithiasis Patients - Bakrun, Muhammad Iqbal Maulana; Rahman, Muhammad Aynur; Handoyo, Dimas Bintoro Kresna Yustisia (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2025)
Introduction. The increasing prevalence of nephrolithiasis in several countries in recent years has made it a serious public health concern. Three days is the typical duration of stay for nephrolithiasis treatment, so longer length of stay will burden society in various ways, especially in terms of expensive costs. This study aims to determine the relationship between the length of stay patients with nephrolithiasis at RSU PKU Muhammadiyah Mojoagung and gender, age, and body mass index. Methods. Descriptive analytic with a cross-sectional design is used in this research, applying the method of consecutive sampling. The chi-square statistical test will be used to assess the data in both univariate and bivariate formats. This research was carried out at RSU PKU Muhammadiyah Mojoagung on inpatients diagnosed with nephrolithiasis within 2023. Results. In this study, 111 patients were included, including 61 men and 50 women. Of the patients, 46.8% were between the ages of 45-65 years old, and the major criteria is non-obesity (64,9%). The patients had a stay of at least 4 days. According to Chi Square Test analysis, body mass index and length of stay have a significant correlation (p=0.012). Meanwhile, there was no correlation between age (p = 0.548) and gender (p = 0.089) with length of stay. Conclusion. Body mass index has correlation with length of stay in nephrolithiasis patients at RSU PKU Muhammadiyah Mojoagung, while gender and age has no correlation with length of stay of nephrolithiasis patients. Keywords: age, body mass index, gender, length of stay, nephrolithiasis patients